Language Socialization in Digitally Mediated Collaborative Writing: Evidence from Disciplinary Peer and Teacher Feedback. (April 2020) - Hafner, Christoph A.; Yu, Cindy
This study examines the question of how the feedback of peers and teachers on a collaboratively written student text, mediated by track changes and commenting functions in Microsoft (MS) Word, can act as a form of socialization into an academic or professional discipline. It focusses on a collaboratively written legal memorandum, authored by students of law engaged in the practice of 'mooting', i.e. the conduct of mock trials, an activity which requires the development of persuasive legal arguments, both in written and spoken form. This article reports on an ethnographic study of the language socialization observed in a team of law students in Hong Kong, as they went about writing a memorandum for a high-stakes, global arbitration mooting competition. This team was observed over a period of approximately eight months, the first three of which were dedicated to the writing of a 35-page memorandum. The team produced a total of 12 drafts of this memorandum. These drafts were reviewed by the students themselves and the legal academic tutors responsible for training the team, with feedback recorded in MS Word. This article presents a multiple case study of participants in the writing process, noting coaching, peer mentoring and editing roles adopted. The analysis shows how the digitally mediated collaborative writing process supported the socialization of students into the disciplinary culture of the law. The analysis identifies socializing feedback on research process, disciplinary content, discourse and lexico-grammar, and also finds that socializing functions were performed by both experts and novices in the community of practice.